POLA KOMUNIKASI KELUARGA DALAM PEMBENTUKAN KEPRIBADIAN ANAK - Siti Rahmah (UIN Antasari Banjarmasin, 2019)
Humans are social creatures who need a good relationship with other people, and have the urge to relate to other people and other impulses such as curiosity, self-actualization, and so on, it will be discarded by communicating with each other. Because humans can always develop and be able to carry out community life, of course, with communication, which can be done at any time, when, by whom and with anyone. Likewise with communication for a child in a family who has work to be used in the community. Parents in a family become a figure for children in the form of the same thing, behavior, speech words formed by parents of parents. The key pattern of communication in the family that is built will affect the parenting style of the children. With good communication patterns will create good parenting patterns, the formation of children in the family form as an effort of parents for the virtue of behaving that must be done early is the basis of education. The formation of awareness as the basis of education is a manifestation of the formation of a child's personality.